COVID-19 MOLECULAR-BASED TESTING CAPACITY IN FIVE CUSTOMARY AREAS OF PAPUA - Clara Imaniar; Mirna Widiyanti (Indonesian Journal of Health Administration, 2022)
Background: COVID-19 (Corona Virus Disease-19) is a disease that emerged at the end of December 2019 and was declared a world pandemic by the WHO (World Health Organization) in March 2020. The gold standard for testing for covid-19 until now is molecular-based virus detection with RT-PCR (Real Time-Polymerase Chain Reaction) and TCM (Molecular Rapid Test). In the early of this pandemic, Indonesia, especially Papua, still had difficulty examining COVID-19 due to limited laboratories that could carry out these tests. Aims: This study aimed to see the laboratory's ability from various regencies representing five customary Papuan areas Methods: This research was a descriptive study that uses primary data and secondary data collected from the Provincial and Regency Papua  COVID-19 Response Acceleration Task Force and the representative hospitals of 5 customary Papuan areas (Saireri, Ha anim, Mee Pago, Lapago, Mamta) Results: There are several challenges and things that need to be considered by all stakeholders involved in examining COVID-19 in Papua so that the examination capacity can be maximally increased. Conclusion: Regency that only has GeneXpert are recommended to have qPCR so that the acceleration of COVID-19 testing in Papua Province can be carried out. The qPCR can be procured in several cities/regencies within one customary area so that sample delivery can be done more quickly without having to send samples to Jayapura City